Revertant mosaic fibroblasts in recessive dystrophic epidermolysis bullosa. (1st December 2019) - Twaroski, K.; Eide, C.; Riddle, M.J.; Xia, L.; Lees, C.J.; Chen, W.; Mathews, W.; Keene, D.R.; McGrath, J.A.; Tolar, J.
Summary: Background: Revertant mosaicism has been described previously in recessive dystrophic epidermolysis bullosa (RDEB), manifesting as regions of skin with normal mechanical and biological characteristics. Here we report the discovery of revertant dermal fibroblasts, unique in that all other documented cases of revertant mosaicism occur in epidermal keratinocytes. Objectives: To determine the cause of revertant mosaicism found in a patient with RDEB from isolated epidermal keratinocytes and dermal fibroblasts in blister and mosaic skin regions. Methods: Skin biopsies were taken from blister and mosaic skin regions of a patient with RDEB. Allele identification was confirmed and the type VII collagen (C7) content and COL7A1 expression profile of isolated keratinocytes and fibroblasts was determined. Results: Keratinocytes isolated from the mosaic area had a slight increase in C7, although overall expression of COL7A1 was unchanged between blister and mosaic fibroblasts. Differential allele expression was identified in blister and mosaic fibroblasts using targeted RNA sequencing (TREx), where the allele harbouring a point mutation was preferentially expressed over that containing a frameshift mutation. A crossing over event was identified in mosaic fibroblasts that was not present in blister fibroblasts, yielding a functional COL7A1 allele in a subset of cells. Conclusions: In documenting a novel case of revertant mosaicism in RDEB, we have identified dermal fibroblasts as having the capacity to correct blistering functionally. We have also pioneered the use of TREx in quantifying allele‐specific expression. Using fibroblasts instead of keratinocytes for RDEB therapies offers advantages in the local and systemic therapy of RDEB. What's already known about this topic? Revertant mosaicism has been previously documented in patients with recessive dystrophic epidermolysis bullosa (RDEB), however, it has only been found in epidermal keratinocytes. What does this study add? We have demonstrated that COL7A1 gene reversion in dermal fibroblasts occurs and is able to form functional skin in a patient with RDEB. Additionally, we have pioneered a new application for targeted RNA sequencing in quantifying allele‐specific expression in fibroblasts and keratinocytes. What is the translational message? This opens up possibilities for using fibroblasts as local and systemic therapy for patients with RDEB.